Acute Vascular Pathology of the Eye as a Complication of the Past COVID-19 Infection. Clinical Observations - T. V. Gavrilova; A. P. Sergienko; M. V. Chereshneva (Oftalʹmologiâ)
Ophthalmological manifestations in COVID-19 infection are diverse, manifesting themselves in all anatomical structures of organ of vision, they occur both in the acute period of the disease and in the post-COVID period. Currently, the literature describes changes in the anterior segment of the eye more often, and also there are publications describing pathological changes in the posterior segment, and acute vascular pathology of the retina after COVID-19 infection in particular. It has been established that the comorbid background of the patient is of great importance in the development and the course of the disease. These findings are also confirmed by our two clinical observations of acute ocular vascular pathology after COVID-19. In the first case, retinovasculitis of the right eye complicated by thrombosis of the inferior temporal branch of the central retinal vein was described. The development of vascular pathology of the eye in this case was observed 1.5 months after the onset of the first symptoms of COVID-19 infection. The patient promptly turned to an ophthalmologist and was hospitalized to an eye hospital, where she received anti-inflammatory, hemostatic, anticoagulant, antibacterial, angioprotective, antioxidant therapy. As a result of treatment — the improvement of condition, restoration of visual functions. In the second presented case, we observed the development of an acute ischemic circulatory disorder of the retina of the left eye (thrombosis of the central retinal vein) 2.5 months after the onset of the disease with a new coronavirus infection. The treatment in an ophthalmological hospital included: steroid and non-steroidal anti-inflammatory drugs, antibiotics, mydriatics, haemostatics, angioprotectors, antioxidants, anticoagulants, vitamins. On discharge from the hospital, there was a slight improvement, but after 2 months, the condition of the left eye worsened again. The pathology of the organ of vision proceeded with the development of complication — secondary neovascular glaucoma of a refractory nature with an outcome to subatrophy of the eyeball. It was facilitated by the comorbid background of the patient: hypertension, type 2 diabetes mellitus, dyslipidemia.Based on the results of the analysis of clinical observations, the specific features of ophthalmological changes, their severity and dynamics on the background of comorbidity and the received therapy were established. The relationship between COVID-19 infection and complications of the organ of vision has been shown.